Intestinal Microbiota Mediates High-Fructose and High-Fat Diets to Induce Chronic Intestinal Inflammation - Tan, Rong; Dong, Huiwei; Chen, Zhengshan; Jin, Min; Yin, Jing; Li, Haibei; Shi, Danyang; Shao, Yifan; Wang, Huaran; Chen, Tianjiao; Yang, Dong; Li, Junwen (Frontiers in Cellular and Infection Microbiology, 2021)
An unhealthy diet has been linked to increased incidence of chronic diseases. To investigate the relationship between diet and intestinal inflammation, mice in two experimental groups were fed on a high-fat diet or high-fructose diet, respectively. The result showed that the defecation volume of the experimental groups was significantly reduced compared with that of the control group, and the levels of pro-inflammatory cytokines (interleukin (IL)-1β and IL-6) and IgG in serum were increased significantly. In addition, inflammatory cell infiltration was observed in intestinal tissue, indicating that a high-fructose or high-fat diet can lead to constipation and inflammation. Further analysis showed that the microbial composition of the experimental groups changed significantly, including a decrease of the Bacteroidetes/ Firmicutes ratio and increased levels of Bacteroides, Akkermansia, Lactobacillus, and Ruminococcus, which might be associated with inflammation. The results of pro-inflammatory metabolites analysis showed that the levels of arachidonic acid, stearic acid, and indoxylsulfuric acid were significantly increased in the experimental groups, which were related significantly to Bacteroides, Enterococcus, and Akkermansia. Meanwhile, the content of 5-hydroxytryptamine (5-HT) was significantly decreased, which might cause constipation by reducing intestinal peristalsis. Moreover, transplantation of fecal bacteria from inflammatory mice caused constipation and inflammation in normal mice, which could be relieved by feeding a normal diet. The results of the present study indicated that changes in intestinal microbiota and microbial metabolites may underlie chronic intestinal inflammation and constipation caused by high-fructose and high-fat diets.